ANALYSIS OF PHYSICAL ACTIVITY TO IMPROVE STUDENTS BASIC MOVEMENT SKILLS PHYSICAL LITERACY BASED PRIMARY SCHOOL - Ardiana , Pradipta Ahdha (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Abstract This literature review study is based on this The current education pattern cannot accommodate the needs of each individual to grow optimally. Most current education patterns do not provide enough space for students' uniqueness in carrying out physical activities. Mastery of basic movements needs to be given to children in the form of physical activity. Physical activity that is designed needs to increase and stimulate children to move without compulsion. The physical activity provided can be in the form of Physical Literacy . The literature review method was carried out on three articles obtained from a number of databases, PubMed, EBSCO, and Springer Link. Keywords for searching articles are physical activity, physical literacy , basic movement skills, physical literacy . Researchers use "AND" as a Boolean operator. The results of the literature review are that the development of a physical activity model to improve elementary school students' basic movement skills is based on physical literacy. The results of the review article are: 1) Physical activity improves health, 2) Good physical literacy knowledge in children aged 7-12 years, 3) Developing physical literacy. The conclusion from the literature review is that understanding physical activity based on the concept of physical literacy can improve health. A high understanding of physical literacy is related to the holistic development of children aged 7-12 years, namely if a person's body is healthy then they will grow and develop optimally. Traditional games can develop elementary school students' physical literacy. These results are based on the improvement achieved by students in the aspects of understanding how to perform movements, movement skills and enjoyment. Keywords: Physical activity, basic movement abilities and Physical Literacy